MGIMO(U) School of Post Soviet Studies - S. I. Chernyavskiy (Vestnik MGIMO-Universiteta)
The article evaluates the history and current work of Center for Post-Soviet Studies - one of analytical subdivisions of MGIMO (U) Institute of International Research.